2018
DOI: 10.6002/ect.2015.0257
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The use of inhibitors of mammalian target of rapamycin is associated with adverse pulmonary effects. Although sirolimus-related pneumonitis has been well described, reports on pneumonitis with everolimus are scarce. We report a case of everolimusinduced pneumonitis in a renal transplant recipient 5 years after initiation of everolimus treatment, and we also review the literature regarding everolimusinduced pneumonitis in renal transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Subsequently, chest imaging with X-ray and CT scans showed varying pulmonary infiltrates in these patients [5,6,14]. Interestingly, plasma serum levels of everolimus are suspected to play a role in pulmonary toxicity in solid organ transplant, and several of the reported liver transplant serum levels were either slightly below or within therapeutic levels of 5.0 to 12.0 ng/mL [5,[10][11][12]. In the reported liver transplant cases, everolimus was eventually discontinued and patients were treated with or without corticosteroids.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Subsequently, chest imaging with X-ray and CT scans showed varying pulmonary infiltrates in these patients [5,6,14]. Interestingly, plasma serum levels of everolimus are suspected to play a role in pulmonary toxicity in solid organ transplant, and several of the reported liver transplant serum levels were either slightly below or within therapeutic levels of 5.0 to 12.0 ng/mL [5,[10][11][12]. In the reported liver transplant cases, everolimus was eventually discontinued and patients were treated with or without corticosteroids.…”
Section: Discussionmentioning
confidence: 91%
“…While the mechanism of everolimus-associated pulmonary complications is not understood, some investigators have speculated that mTOR inhibition is associated with activation of the STAT1 gene, leading to increased apoptosis and injury; others theorize that a STAT3 polymorphism may increase the risk of interstitial lung disease with mTOR inhibitors [8,9]. Moreover, studies have also indicated that pulmonary toxicity seen with mTOR inhibitors correlated with higher doses of the medication [10].…”
Section: Introductionmentioning
confidence: 99%